Use of social media as a tool for antibiotics awareness - K Raksha (Apollo Medicine)
Objective: Antimicrobial resistance (AMR) is a global health threat; public perception about AMR is a huge lacuna which many researchers, doctors, and policymakers fail to pay attention to. Infection control is often limited to diagnosis and treatment in hospitals, presentations, and panel discussions. On the other side of the fence, usage of social media to spread information about health care is a common practice among the public today. Twitter is one such online platform.Materials and Methods: This was a cross-sectional tweet-based poll titled “antibiotic awareness survey” for 7 days with five simple yet pertinent questions asked to the participants in the Twitter poll and also to retweet (RT) the questions to their followers. The questions were designed keeping in mind the limitation of tweets on the timeline and the necessity of addressal to the issue among the random group. Results: Seventy-two percent responded saying they procure antibiotics based on doctor's prescription. The most common reason to stop antibiotics for 35% of the participants was symptomatic relief and the perception that it is okay to stop, but 56% said they always complete the course. 52% of the participants said that the treating doctor does not explain to them about the antibiotics while prescribing, but 81% said that the doctor advises them on completing the course. 75% of the participants said that antibiotics are in danger and require regulation, 22% said maybe to an extent. Conclusion: Social media plays a critical role in dissemination of AMR-related information; the unrestricted and unregulated access to knowledge shapes the views and opinions of society. The perception and practices were thus reflected through this weeklong discourse about antibiotics on Twitter, and we doctors of today have a responsible role to play.